Shifting dynamics in Turkish foreign policy in the trans-European space - Baracani, E.; Çalımlı, M. (Palgrave Macmillan, 2019)
This chapter reconstructs Turkey's foreign policy interactions with the key actors in the Trans-European space, during the Justice and Development Party's era, evaluating how they have been mutually influencing and how they have developed over time. Baracani and Çalimli show that in the last years, different factors have contributed to make Turkey less and less attracted by the model represented by the European Union and to shape Turkish foreign policy new activism in and beyond the Trans-European space. © The Author(s) 2019.